2003
DOI: 10.1099/mic.0.26483-0
|View full text |Cite
|
Sign up to set email alerts
|

Gingival epithelial cell signalling and cytoskeletal responses to Porphyromonas gingivalis invasion

Abstract: Porphyromonas gingivalis, an oral pathogen, can internalize within primary gingival epithelial cells (GECs) through an invasion mechanism mediated by interactions between P. gingivalis fimbriae and integrins on the surface of the GECs. Fimbriae-integrin-based signalling events were studied by fluorescence microscopy, and the subcellular localization of integrin-associated signalling molecules paxillin and focal adhesion kinase (FAK), and the architecture of the actin and microtubule cytoskeleton were examined.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
141
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 118 publications
(146 citation statements)
references
References 36 publications
(39 reference statements)
5
141
0
Order By: Relevance
“…The number of the completely internalized beads increased along the incubation time, and reached saturation at 40 min. The kinetics of internalization was found to be quite similar to that of living bacteria reported in previous studies (Yilmaz et al, 2004;Yilmaz et al, 2003).We also examined the localization of a5b1-integrin which was reported to be responsible for the initial binding of P. gingivalis to the cells (Nakagawa et al, 2005;Yilmaz et al, 2002). Consistent with those previous reports, recruitment of a5b1-integrin was observed at the bead internalization site (Fig.…”
Section: Efficient Internalization Of Mvs-coated Beads To Hela Cellssupporting
confidence: 78%
“…The number of the completely internalized beads increased along the incubation time, and reached saturation at 40 min. The kinetics of internalization was found to be quite similar to that of living bacteria reported in previous studies (Yilmaz et al, 2004;Yilmaz et al, 2003).We also examined the localization of a5b1-integrin which was reported to be responsible for the initial binding of P. gingivalis to the cells (Nakagawa et al, 2005;Yilmaz et al, 2002). Consistent with those previous reports, recruitment of a5b1-integrin was observed at the bead internalization site (Fig.…”
Section: Efficient Internalization Of Mvs-coated Beads To Hela Cellssupporting
confidence: 78%
“…Reports have documented that paxillin regulation can be directly initiated by pathogen-host cell interactions. For example, bacterial lipopolysaccharide (LPS) and fimbriae of the Gram-negative anaerobe Porphyromonas gingivalis can trigger paxillin phosphorylation (18,52,53). Additionally, the HIV transactivator protein Tat has been demonstrated to activate paxillin; however, this process was not a result of a direct interaction of the virus with the cell, as the Tat protein must be expressed to have a stimulating effect on surrounding cells (16).…”
Section: Discussionmentioning
confidence: 99%
“…35) Moreover, Yilmaz et al reported that fimbriated P. gingivalis cells induce the formation of integrin-associated focal adhesion, with subsequent remodeling of the actin and tubulin cytoskeleton for internalization. 36) To determine whether type-IV pili are involved in invasion by E. corrodens of oral epithelial cells, we performed an invasion assay using a phase variant of strain 23834. It has been reported that E. corrodens exhibits phase variation resulting from a loss of type-IV pili, which is reflected in irreversible morphological changes in colonies, from corroding to non-corroding.…”
Section: Genomic Recombination Reduced Invasion By E Corrodens Of Epmentioning
confidence: 99%